Hybrid TiO2:Au nanostars based polymeric membranes for photocatalytic degradation of ciprofloxacin in water samples. (February 2023) - Zheng, Fangyuan; Martins, Pedro M.; Queirós, Joana M.; Tavares, Carlos J.; Vilas-Vilela, José Luis; Lanceros-Méndez, Senentxu; Reguera, Javier
Abstract: Antibiotics represent one increasingly harmful type of contaminant of emerging concern in treated and non-treated water. They cause the generation of antibiotic-multiresistant organisms, one of the major challenges in current medicine. Plasmonic-photocatalysis using solar energy represents a promising solution for their removal with low energy consumption. Its successful application requires the improvement of photocatalysts' efficiency under sunlight and the development of robust, durable, and efficient substrates for photocatalysts immobilisation. In this work, hybrid TiO2 :Au nanostars were initially synthesised. Then, two porous membranes were prepared to support this nanocatalyst based on poly (vinylidenefluoride- co -hexafluoropropylene) polymer. Doctor blade and salt leaching casting methods, combined with temperature-induced phase separation, were used to generate membranes with high porosity, 80–90%, which was maintained after nanoparticle incorporation (3, 8 and 10 wt%). The photocatalytic activity of the nanocomposite membranes was tested through the degradation of the antibiotic ciprofloxacin under UV and visible radiation. Salt-leaching membranes containing 10 wt% nanoparticles presented the highest degradation efficiencies, 45% under UV and 35% under visible radiation. In contrast, doctor blade membranes showed 36% and 32% degradation efficiencies, respectively. The reusability of the membranes was assessed in repeated cycles, presenting an average efficiency loss of only 2% after three uses. Finally, the reusability of these membranes was also tested in treated effluent water matrixes, presenting similar, or even better, degradation efficiencies, and a minimum reusability efficiency lost 0–1%. The results demonstrate that these membranes are a promising alternative for the degradation of a wide variety of contaminants under sunlight radiation. Graphical abstract: Image 1 Highlights: Synthesised TiO2 :Au nanostars enhance sunlight absorption at visible wavelengths. High control on polyvinylidene fluoride porous membrane morphologies. Efficient degradation of ciprofloxacin under UV and visible radiation. Membranes with 10 wt% of nanoparticles maintained efficiency after many uses. Reusable membranes were fully functional in real water effluents.